The electrical characteristics of the direct current welding arc and the design and testing of a D.C. welding generator - Cardwell, Geoffrey Robert (Department of Electrical Engineering, 2016)
The machine to be used as the power source is first evaluated by means of the usual indirect tests. These tests confirm that the machine has acceptable steady state characteristics for welding and a basic excitation control circuit is employed to give the desired control of the output from the generator. The initial welds made are very unsatisfactory and attempts to improve the weldability by modifying the characteristics of the control circuit are unsuccessful. Only by increasing the time constant of the output circuit through the addition of series inductance can the desired improvements be obtained. At this stage an investigation into the electrical characteristics of the D.C. welding arc is carried out. This reveals the extreme transient nature of the arc load on the generator and design criteria for good weldability can now be employed to achieve satisfactory results. Field excitation of the alternator is varied by means of current feedback from the output circuit which is able to produce high welding currents when using a low voltage reference supply from a battery. The initial evaluation has to be repeated on a new design of alternator and tests indicate that a suitable A.C. reactor in the output from the alternator will produce a more desirable transient response to the arc load. Different types of current control are tried in order to obtain the best type and range of welding characteristics. The design of the most important components which make up the welding generator is discussed and the proposed layout for the complete set is given.